(untitled) (International Journal of Innovative Technologies in Economy, 2020)
The purpose of the scientific research is to form the process of personnel provision at the agricultural enterprise and personnel management of the agricultural enterprise to increase its efficiency, identifying key components of personnel provision and their impact on the effective activity of the enterprise. As a result of the study, the place of Ukraine as a country-exporter of agricultural products, especially cereals, in the world space was shown. The market trends of the agricultural sector of Ukraine for 2014 – 2019 are analyzed. The key problems of the agricultural labor market are identified. An organizational scheme-algorithm for the formation of the process of effective personnel provision at agricultural enterprises is proposed, considering the main stages, which is based on a systematic approach. Within the framework of the system-process approach, it is proposed to implement the PDCA methodology, which allows effectively manage the activities of an enterprise on a systematic basis for further effective management of the personnel provision at an agricultural enterprise. Also, significant components of the personnel provision process are identified and, using the analytic hierarchy process (AHP), the influence of these components on the key performance indicators of each individual enterprise are revealed.